Domain pinning and valence state switching in Pb(Zr0.2Ti0.8)O3/La0.8Sr0.2MnO3 heterostructures - Su, Dong; Vaz, Carlos A. F.; Segal, Y.; Walker, Fred; Ahn, Chong H.; Han, M-G; Sawicki, Monica; Broadbridge, Christine (Microscopy and Microanalysis, 2011)
Keywords: dept.phy

Valence electron energy-loss spectroscopy of ultrathin SrTiO3 films grown on silicon (100) single crystal - Su, Dong; Yang, Bo; Jiang, Nan; Sawicki, Monica; Broadbridge, Christine; Couillard, M; Reiner, James W; Walker, Fred; Ahn, C H; Zhu, Yimei (Applied Physics Letters, 2010)
Valence electron energy-loss spectroscopy is used to investigate the plasmon excitations of ultrathin SrTiO3 sandwiched between amorphous Si and crystalline Si. Two plasmon excitations were observed, one at 15.8 eV and the other at 28.7 eV. Our calculations, based on dielectric-function theory, suggest that the former peak originates from the coupling of the Si layers and is related to the geometry of the structure, and the latter peak results from the SrTiO3 bulk plasmon after a redshift. Our findings demonstrate the value of valence electron energy-loss spectroscopy in detecting a local change in the effective electron mass. © 2010 American Institute of Physics.
Keywords: Amorphous Si; Amorphous silicon; Crystalline Si; Dissociation; Electron energy loss spectroscopy; Electron scattering; Electrons; Function theory; Plasmon excitations; Plasmons; Red shift; Si layer; Silicon (100); Silicon wafers; Single crystals; SrTiO; Strontium alloys; Ultra-thin; Valence electron energy-loss spectroscopies; dept.phy

Origin of 90° domain wall pinning in Pb(Zr0.2Ti0.8)O3 heteroepitaxial thin films - Su, Dong; Meng, Qingping; Vaz, Carlos A. F.; Han, Myung-Geun; Segal, Y.; Walker, Fred; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H. (Applied Physics Letters, 2011)
We describe a transmission-electron-microscopy study of the ferroelectric domains in an epitaxial Pb(Zr0.2Ti0.8)O3 (PZT) film grown on La0.7Sr0.3MnO3/SrTiO 3(001). We directly observe the pinning of 90 domain walls by pairs of misfit dislocations, respectively, with Burgers vectors a [100] and a [001]. Model calculations based on the elastic theory confirm our finding that, in addition to the depolarization field surrounding the dislocation, the strain field of misfit dislocation-pairs plays the primary role in the formation and pinning of a domains. © 2011 American Institute of Physics.
Keywords: Depolarization fields; Domain walls; Domain-wall pinning; Elastic theory; Epitaxial growth; Ferroelectric domains; Ferroelectricity; Heteroepitaxial thin films; Heterojunctions; Lanthanum compounds; Lead; Manganese oxide; Model calculations; PZT; Strain fields; Zirconium; dept.phy

The atomic structure and polarization of strained SrTiO3/Si - Kumah, Divine; Reiner, James W.; Segal, Y.; Kolpak, Alexie M.; Zhang, Zhizhi; Su, Dong; Zhu, Yimei; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2010)
For thin film devices based on coupling ferroelectric polarization to charge carriers in semiconductors, the role of the interface is critical. To elucidate this role, we use synchrotron x-ray diffraction to determine the interface structure of epitaxial SrTiO3 grown on the (001) surface of Si. The average displacement of the O octahedral sublattice relative to the Sr sublattice determines the film polarization and is measured to be about 0.05 nm toward the Si, with Ti off-center displacements 0.009 nm away from the substrate. Measurements of films with different boundary conditions on the top of the SrTiO3 show that the polarization at the SrTiO3 /Si interface is dominated by oxide-Si chemical interactions. © 2010 American Institute of Physics.
Keywords: Atomic structure; Chemical interactions; Crystal atomic structure; Different boundary condition; Ferroelectric polarization; Interface structures; Polarization; Semiconducting silicon compounds; Silicon; SrTiO; Strontium alloys; Sub-lattices; Synchrotron x ray diffraction; Thin film devices; X ray diffraction; dept.phy